Electrochemical amination of para-chloroaniline - Yu.A. Lisitsyn (Учёные записки Казанского университета: Серия Естественные науки)
The process of cation-radical amination of para-chloroaniline using hydroxylamine and the Ti(IV)/Ti(III) mediator system was studied in aqueous solutions of 9–17 M H2SO4. The substitution products in these media are 4-chloro-1,3-, 4-chloro-1,2-phenylenediamines, as well as para-phenylenediamine. An increase in the acid concentration was accompanied by a raise in the overall efficiency of the electrochemical process with a decrease in the current yields of the last two diamino compounds. In 17 M H2SO4, the yield and mass fraction of 4-chloro-1,3-phenylenediamine reached 75.2 and 99.7%, respectively.